PENGARUH FAKTOR INTERNAL DAN BI RATE TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2012-2015 - FITRIANA, SELVIA (Jurnal Ilmu Manajemen (JIM), 2017)
This purpose of this reserch was to analyze the influence of internal factors and macroeconomic variables on profitability at Bank Syariah in Indonesia 2012-2015. Profitability proxy with Return on Assets (ROA) is influenced by Non Performing Financing (NPF), Financing To Deposit Ratio (FDR), Liquid Asset to Deposit (LAD), and macroeconomic variable is BI Rate. The sample used in this study is Bank Syariah which publishes financial statements and did not experience loss during the study period 2012-2015. The data analysis technique used is multiple linear regression analysis with the help of SPSS program. The results showed that NPF variables negatively affect profitability, because the magnitude of NPF resulted in the loss of income opportunities from financing, thus lowering ROA. And the BI Rate variable has a negative effect on profitability, the increase of BI interest rate will affect the operational activities and decrease the income of Syariah Bank in Indonesia. CAR variables do not affect ROA because the amount of capital used for investment is not used to earn profit. The DPK variable does not affect the ROA because the amount of profit obtained from financing is offset by an increase in bank operating costs. The FDR variable does not affect ROA because the amount of financing disbursed has an impact on the increased risk of bad loans. While LAD variable does not affect ROA because profit obtained from financing activity is bigger than bank liquidity. Keywords: Profitabilitas, Sharia Bank, Internal Bank, Macroeconomy